Pengaruh Kebijakan Dividen dan Nilai Perusahaan terhadap Harga Saham pada Perusahaan Indeks LQ45 Periode 2019-2024 - Amita Fatmasari Dewi; Cynthia Eka Violita; Achmad Zaki; Devika Eka Cherly (Indonesian Journal of Applied Accounting and Finance, 2026)
This paper examines how dividend policy and corporate worth affected the stock prices of LQ45-listed firms between 2019 and 2024. The Dividend Payout Ratio (DPR) serves as the metric for dividend policy, while the Price to Book Value (PBV) ratio represents firm value. This quantitative study applies panel data regression, utilizing Chow, Hausman, and Lagrange multiplier tests to determine the most fitting econometric model. Individual variable significance is assessed via $t$-tests to isolate partial effects on stock prices. The findings indicate that while the DPR has a negligible effect on stock prices, PBV plays a much more prominent role. Consequently, investors appear to favor overall firm value over dividend payouts during decision-making. However, a low yet statistically significant coefficient of determination highlights that external, unmodeled factors heavily influence stock prices. The study concludes that firm value is vital to stock price dynamics and advises future researchers to incorporate macroeconomic indicators to boost the model's predictive strength.